Consumo de substâncias psicoativas em adultos do sexo masculino privados de liberdade - Prates, Priscila Flores (2016)
Drug addiction is an age-old problem, but currently only public policies have been concerned with interventions to users. Drug use by inmates is a serious health problem so that there is a need for studies to seek alternative solutions. This research aimed to investigate the consumption of psychoactive substances in a sample of inmate male adults. We used the Alcohol, Smoking and Substance Involvement Screening Test (ASSIST), which evaluates the consumption of drugs in the last three months prior to testing. The test was applied to 139 inmates aged from 19 to 58 years from prisons in southern Brazil. The results showed high rate related to the use of tobacco, alcohol, marijuana and cocaine/crack and that the correlations between the use of different drugs were positive and statistically significant. We conclude that there is a strongly established association between drug use and deprivation of liberty in that context, causing health and safety problems. Furthermore, it is important to expand literature with new studies to provide more data that can support specific interventions to the needs of inmates.